Age as a factor in Russian EFL teacher attitudes towards literature in language education. (March 2019) - Calafato, Raees; Paran, Amos
Highlights: Younger EFL teachers do not use literature as frequently in their lessons. Older EFL teachers encountered literature more often as learners. Enjoyment of reading in both the L1 and L2 show declines among younger EFL teachers. The majority of teacher participants agreed that literature benefitted language learning.